The agricultural and therapeutic potential of Lavatera thuringiaca (L.) - Staniak, Mariola; Kowalska, Iwona; Amin, Ruhul; Sharifi-Rad, Javad; Czopek, Katarzyna; Stępień-Warda, Anna (Acta agrobotanica, 2024)
One of the poorly recognized plant species well adapted to cultivation in temperate climate conditions is Lavatera thuringiaca L. It is a common species in Europe, but so far has not found much economic use. Few literature data report its high production potential, favorable chemical composition of biomass, resistance to adverse stress conditions, and medicinal properties. The biomass can be used for fodder and energy purposes and as forage for bees and other pollinators. L. thuringiaca can also be useful for the management of fallow soils or marginal land and for the reclamation of contaminated land. In turn, the presence of biologically active compounds offers opportunities for its use in medicine. Wider diversification of cultivated species is a key to ensuring food security and economic sustainability, especially in view of the observed climate change. In this context, an extensive review of literature dealing with taxonomic studies, morphological diversity and biological properties of L. thuringiaca, and the potential for multipurpose use of this species has been carried out.